Male reprotoxicity and endocrine disruption - Campion, Sarah (2012)
Mammalian reproductive tract development is a tightly regulated process that can be disrupted following exposure to drugs, toxicants, endocrine disrupting chemicals or other compounds via alterations to gene and protein expression or epigenetic regulation. Indeed, the impacts of developmental exposure to certain toxicants may not be fully realized until puberty or adulthood when the reproductive tract becomes sexually mature and altered functionality is manifested. Exposures that occur later in life, once development is complete, can also disrupt the intricate hormonal and paracrine interactions responsible for adult functions, such as spermatogenesis. In this chapter, the biology and toxicology of the male reproductive tract is explored, proceeding through the various life stages including in utero development, puberty, adulthood and senescence. Special attention is given to the discussion of endocrine disrupting chemicals, chemical mixtures, low dose effects, transgenerational effects, and potential exposure-related causes of male reproductive tract cancers.